Nurses’ self-assessed moral courage in primary health care : a cross-sectional study - Pajakoski, Elina (My University, 2021)
Background: Moral courage refers to a particular kind of courage, acting according to one’s own ethical principles even when there is a risk of negative consequences for the acting individual. Research on moral courage is relatively limited, although it is a crucial way to increase quality of nursing care and nurses’ work-related well-being. Purpose: To analyse nurses’ self-assessed moral courage and which individual background factors are associated with it in primary health care. Methods: A cross-sectional design, using a self-assessment instrument, Nurses’ Moral Courage Scale (NMCS). A Likert 1-5 scale was applied in all items and overall moral courage was assessed with VAS 0 to 10. Moral courage was analysed in a total sum of all 21 items and four sub-scale sum variables, representing the dimensions of moral courage. Findings: A total of 205 primary health care nurses completed the questionnaire (response rate 30%). The mean of moral courage in the total sample was 4,16 (SD 0,58). The higher the participants assessed their knowledge base in ethics, the higher was their moral courage in all sub-scales. The differences were statistically significant. Also encountering more ethical dilemmas, self-learned ethics and knowledge of ethics obtained from nursing practice meant more moral courage. These differences were statistically significant. Conclusion: Overall the participants assessed their moral courage to a rather high level, which is in line with earlier results in this area. The novelty of these results was in the context of primary health care and strong associations between moral courage and knowledge base in ethics, sources from which the knowledge was obtained and encountering more situations requiring moral courage. However, age and work experience did not always mean higher level of moral courage. This supports the viewpoint that moral courage is a valuable personal characteristic and a human virtue, which can be strengthened with motivation and education.

Tausta: Moraalinen rohkeus viittaa tietynlaiseen rohkeuteen, jossa yksilö toimii omien eettisten periaatteidensa mukaisesti huolimatta hänelle mahdollisesti koituvista negatiivisista seurauksista. Moraalista rohkeutta on tutkittu suhteellisen vähän, mutta se on keskeinen tekijä hoidon hyvän laadun ja hoitotyöntekijöiden työhyvinvoinnin edistäjä. Tarkoitus: Analysoida hoitotyöntekijöiden itsearvioitua moraalista rohkeutta ja siihen yhteydessä olevia yksilöllisiä taustatekijöitä perusterveydenhuollossa. Menetelmät: Poikittaistutkimus, jossa oli itsearviointimittarina Nurses’ Moral Courage Scale (NMCS). Kysymyksiä annettiin vastaus Likert 1-5 -asteikolla. Yleistä moraalista rohkeutta arvioitiin VAS 0-10 -asteikolla. Moraalista rohkeutta analysoitiin mittarin summamuuttujalla (21 kysymystä) sekä osasummamuuttujilla, jotka perustuivat moraalisen rohkeuden ulottuvuuksiin. Tulokset: Kyselyyn vastasi 205 hoitotyöntekijää. Vastausprosentti oli 30. Moraalisen rohkeuden keskiarvo koko otoksessa oli 4,16 (keskihajonta 0,58). Mitä korkeammalle osallistujat arvioivat etiikan tietopohjansa, sitä korkeampi oli heidän moraalinen rohkeutensa kaikissa alasummamuuttujissa. Erot ryhmien välillä olivat tilastollisesti merkitseviä. Myös eettisten ongelmien kohtaaminen useammin, etiikan itseopiskelu sekä etiikan tietojen oppiminen käytännön hoitotyössä lisäsivät moraalista rohkeutta tilastollisesti merkitsevästi. Johtopäätökset: Osallistujat arvioivat moraalisen rohkeutensa yleisesti melko korkealle tasolle, mikä on linjassa aiempien tutkimusten kanssa. Erityistä tämän tutkimuksen tuloksissa olivat perusterveydenhuollon konteksti ja vahvat yhteydet moraalisen rohkeuden ja etiikan tietopohjan, etiikan tietojen lähteiden sekä moraalista rohkeutta vaativien tilanteiden kohtaamisen välillä. Ikä ja työkokemus eivät aina nostaneet moraalisen rohkeuden tasoa. Tämä tulos tukee näkemystä moraalisesta rohkeudesta yksilön arvokkaana piirteenä ja hyveenä, jota voidaan vahvistaa motivaation ja koulutuksen avulla.
Keywords: moral courage, nurse, primary health care, ethical competence, background factors